Monetary Expansionism, Global Commodity Prices, and Global Inequality - Jongchul Kim (Monetary Expansionism, Global Commodity Prices, and Global Inequality, 2025)
An early analysis of the imperialist implications of the surge of global commodity prices was conducted in 2014 by Jonathan Nitzan and Shimshon Bichler. However, their analysis did not consider how the US monetary and fiscal expansionist policies have contributed to the rise of global commodity prices. This article fills this gap. Arguably, under the current international fiat money system established in the early 1970s, the US has had the opportunity to use artificial money-creation mechanisms to enjoy the wealth produced by people outside the US without cost. This article argues that the US monetary and fiscal expansionist policies, including quantitative easing, are cases where the US takes advantage of such an opportunity and that the free transfer of wealth is a cause of the surge in global commodity prices.
Keywords: P1; E31; E5; E62; F4; 330; capital as power; commodities; fiscal policy; imperialism; inflation; monetary policy; money; prices; United States